ORGANIZATION OF EDUCATIONAL COLLABORATION IN INTERNET - A. V. Anisimov; I. O. Zavadsky (Ìнформаційні технології в освіті)
The purpose and usage methodology of network collaborative learning software are discussed. The Internet collaborative learning system “Informatics” is described.